2008
DOI: 10.1016/j.ijrobp.2007.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Differential Efficacy of Combined Therapy With Radiation and AEE788 in High and Low EGFR-Expressing Androgen-Independent Prostate Tumor Models

Abstract: Purpose-To determine the efficacy of combining radiation (XRT) with a dual EGFR/VEGFR inhibitor, AEE788, in prostate cancer models with different levels of EGFR expression. Methods and Materials-Immunoblotting was performed for EGFR, phosphorylated-EGFR (p-EGFR), and p-AKT in prostate cancer cells. Clonogenic assays were performed on DU145, PC-3 and HUVEC cells treated with XRT+/−AEE788. Tumor xenografts were established for DU145 and PC-3 on hindlimbs of athymic nude mice assigned to four treatment groups: 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
(47 reference statements)
2
11
0
Order By: Relevance
“…1 and 3, DER 37 $ 1.3-1.8) is lower than often observed with anticancer drug sensitization. Nevertheless, the differential radiosensitization is significant as compared with, for example, clinically used and experimental EGFR targeting sensitizing agents such as erlotinib (40) or C225 (41,42). Our in vivo experiments confirm that SR48692 treatment combined with radiation causes significant reduction in tumor growth (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…1 and 3, DER 37 $ 1.3-1.8) is lower than often observed with anticancer drug sensitization. Nevertheless, the differential radiosensitization is significant as compared with, for example, clinically used and experimental EGFR targeting sensitizing agents such as erlotinib (40) or C225 (41,42). Our in vivo experiments confirm that SR48692 treatment combined with radiation causes significant reduction in tumor growth (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Atkinson et al reported the successful detection of the alkylaminoanthraquinone AQ4N (banoxatrone) in tumor xenografts by MALDI-MSI (34). The distribution of the multiple-receptor tyrosine kinase inhibitor AEE788 in rodent prostate cancer models was analyzed by MALDI-MSI (35). The tyrosine kinase inhibitors erlotinib and gefitinib have been analyzed, after depositing single droplets of drugs on tissue slices of planocellular lung carcinoma, adeno-carcinoma and large cell lung carcinoma (36)(37)(38).…”
Section: Mass Spectrometry Imaging (Msi) Mass Spectrometry Imaging (Msi)mentioning
confidence: 99%
“…The ability to directly compare MALDI imaging results with conventional immunohistochemistry techniques not only allows researchers to determine if the drug has reached the target site of action, but also enables elucidation of potential mechanisms surrounding the specific distribution. Lastly, Huamani et al combined the use of Doppler ultrasonography, immunohistochemistry, and MALDI imaging to determine the efficacy of combining radiation (XRT) with a dual epidermal growth factor receptor (EgFR)/vascular endothelial growth factor receptor inhibitor, AEE788, in prostate cancer models with different levels of EgFR expression [100]. Four treatment groups were examined: control, AEE788-dosed tumors, XRTtreated tumors, and tumors treated with a combination of AEE788 and XRT.…”
Section: Imaging Drugs and Metabolites In Individual Organs/tissuesmentioning
confidence: 99%